2001
DOI: 10.1021/bi002318+
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Metabolic Inferences from the Binding of Substrate Analogues and Products to Arginase,

Abstract: Arginase is a binuclear Mn(2+) metalloenzyme that catalyzes the hydrolysis of L-arginine to L-ornithine and urea. X-ray crystal structures of arginase complexed to substrate analogues N(omega)-hydroxy-L-arginine and N(omega)-hydroxy-nor-L-arginine, as well as the products L-ornithine and urea, complete a set of structural "snapshots" along the reaction coordinate of arginase catalysis when interpreted along with the X-ray crystal structure of the arginase-transition-state analogue complex described in Kim et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 72 publications
3
85
0
Order By: Relevance
“…Moreover, two different arginase inhibitors cause reductions in polyamine production as well as cell proliferation. We do find, however, that the NO donor agent, SNAP, is more effective than NOHA or BEC in slowing cell proliferation despite the fact that their potencies as inhibitors of arginase or ODC are quite similar (9,10,(14)(15)(16). Therefore, the ODC enzymatic reaction may be somewhat slower and more rate-limiting than the arginase reaction under certain conditions but, nevertheless, inhibition of either reaction can lower polyamine production and decrease cell proliferation.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Moreover, two different arginase inhibitors cause reductions in polyamine production as well as cell proliferation. We do find, however, that the NO donor agent, SNAP, is more effective than NOHA or BEC in slowing cell proliferation despite the fact that their potencies as inhibitors of arginase or ODC are quite similar (9,10,(14)(15)(16). Therefore, the ODC enzymatic reaction may be somewhat slower and more rate-limiting than the arginase reaction under certain conditions but, nevertheless, inhibition of either reaction can lower polyamine production and decrease cell proliferation.…”
Section: Discussionmentioning
confidence: 74%
“…We have shown that NOHA, the major intermediate in the NO synthase-catalyzed conversion of arginine to NO and citrulline, is a potent inhibitor of both arginase and tumor-cell proliferation (9). Arginase is a binuclear Mn 2ϩ metalloenzyme with a high binding affinity for boronic acid-based arginine analogs (14). BEC is one such analog and has been reported to be more potent than NOHA as an arginase inhibitor (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, structures of the inhibitor complexes of rat liver arginase I (28,30,(35)(36)(37) and human nonhepatic arginase II (17) were reported and B. caldovelox arginase was structurally analyzed in complex with the substrate and its analogs (18). A comparison of the active sites of ureohydrolase superfamily enzymes shows that the hydrolysis site where the guanidinium (or guanidine) group of the substrates binds is well conserved, whereas the peripheral surface regions of the active site deviate most from each other (Fig.…”
Section: Figmentioning
confidence: 99%
“…Consistent with this finding, incubation with L-ornithine increased airway responsiveness in perfused guinea pig tracheal preparations by inducing a deficiency of cNOSderived NO [49]. Although L-ornithine also competitively inhibits arginase activity [32,49,50], the increase in airway responsiveness shows that the inhibitory effect on L-arginine uptake is larger than that on arginase activity [49]. Thus, mutual interactions between NOS and arginase regulate L-arginine homeostasis and NO-synthesis in the airways (Fig.…”
Section: Nitric Oxide Homeostasis and Airway Functionmentioning
confidence: 76%